Analyzing the Thematic Evolution of Policy Design Research - Barbosa de Aguiar, Rafael; Leite Lima, Luciana; Lui, Lizandro (BIB - Revista Brasileira de Informação Bibliográfica em Ciências Sociais, 2022)
Policy design (PD) has received increasing attention over the last few decades. During this period, PD contributed to expanding knowledge regarding the functioning of public policies, its implementation instruments, and its social effects. This review shows the thematic evolution of PD by systematizing the extant literature and grouping its scientific knowledge. Our research question is: how has policy design evolved? Our main contributions are threefold: i) quantify its research and describe its main outputs and evolution; ii) identify past and current trends; and iii) propose future avenues for research. To do so, we mapped the academic literature, drawing on a systematic approach of 184 selected papers. Then, we analyzed these data by conducting a two-level analysis. We noticed that production is geographically uneven and that the field has developed alongside technological evolution and adopts contemporary tools and instruments,